Bedside Table with Hidden Compartment Inspired by Geometric - Kor, Kah Poh; Selimin, Mohamad Ali (Research in Management of Technology and Business, 2023)
Housebreaking and theft are the second-most common property crimes in Kuala Lumpur and Selangor, accounting for 950.9 recorded offences per 100,000 people between 2010 and 2017. Therefore, the present study aims to identify the design criteria, to design and to develop a bedside table with hidden compartment inspired by geometric. The questionnaire was distributed via Google Form to the 60 respondents aged 25 years old and above in Kuala Lumpur to obtain the design criteria. Following that, the design and prototype fabrication processes were carried out in accordance with the design criteria obtained. A final design survey was undertaken to enquire about the wants of potential consumers. In the prototype fabrication, a bedside table with hidden compartment was created utilising MDF with a laminated finish, built-in lighting and charging port features. The hidden compartment has been successful designed by implement the false back button feature. The study has the benefit to prevent items from being stolen during a burglary.